2014
DOI: 10.1007/s10549-014-2849-2
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density and circulating biomarkers in the BIG 1-98 trial comparing adjuvant letrozole, tamoxifen and their sequences

Abstract: Purpose To determine the effects of the BIG 1-98 treatments on bone mineral density. BIG 1-98 compared 5-year adjuvant hormone therapy in postmenopausal women allocated to four groups: tamoxifen (T); letrozole (L); 2-years T, 3-years L (TL); 2-years L, 3-years T (LT). Methods Bone mineral density T-score was measured prospectively annually by dual energy X-ray absorption in 424 patients enrolled in a sub-study after three (n=150), four (n=200), and five years (n=74) from randomization, and one year after tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…However, this drug is ambivalent concerning its target tissues with agonist estrogen effects on bone, endometrium and also liver. This explains its beneficial effects, such as increased mineral bone density [2], and also its side effects such as thromboembolic events [3], increased endometrial cancer events [4] and hot flushes [5].…”
mentioning
confidence: 99%
“…However, this drug is ambivalent concerning its target tissues with agonist estrogen effects on bone, endometrium and also liver. This explains its beneficial effects, such as increased mineral bone density [2], and also its side effects such as thromboembolic events [3], increased endometrial cancer events [4] and hot flushes [5].…”
mentioning
confidence: 99%
“…A sub-study of the BIG 1-98 trial, comparing four 5-year regimens of endocrine therapy, looked at the effect of each regimen on BMD. 31 They found that the sequenced treatment of tamoxifen followed by letrozole had the worst effect on BMD and that letrozole followed by tamoxifen appeared to preserve BMD. They hypothesized that the interruption of tamoxifen combined with the rapid fall in oestrogen levels induced by letrozole promotes an accelerated bone turnover and loss of BMD following the switch as was confirmed by bone turnover biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore it can be questioned into which extend our results are influenced by the positive effect of tamoxifen on bone health. A sub‐study of the BIG 1–98 trial, comparing four 5‐year regimens of endocrine therapy, looked at the effect of each regimen on BMD . They found that the sequenced treatment of tamoxifen followed by letrozole had the worst effect on BMD and that letrozole followed by tamoxifen appeared to preserve BMD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The American Society for Clinical Oncology (ASCO) recommends using the AI for 5 years, or for 2 or 3 years, after previous therapy with tamoxifen (TMX) 4 , where the latter option is prescribed for pre/perimenopausal women 5 . However, reduced estrogen levels increase bone resorption and raise the risk of fracture that occurs after menopause 1,[6][7][8][9] . Clinical guidelines for the management of bone loss associated with AI (AIBL: Aromatase Inhibitor associated Bone Loss) recommends a strict monitoring of bone mineral density (BMD) and other risk factors to assess the need for treatment with anti-resortive therapies 10 .…”
Section: Introductionmentioning
confidence: 99%